Perfectionism and Gender Dynamics in Greta Gerwig’s Barbie and Patty Jenkins’ Wonder Woman - Pitaloka, Roro Meifi; Said, Mashadi; Meidasari, Venny Eka (INFERENCE: Journal of English Language Teaching, 2024)
This study examines the portrayal of perfectionism and gender dynamics in Barbie and Wonder Woman. It utilizes Greimas’s Actantial Model and an intrinsic narrative analysis to explore how both films depict these themes. Barbie and Wonder Woman investigate the societal roots of perfectionism and its effects, offering distinct perspectives on gender roles, expectations, and power structures. A qualitative methodology, applied in this study, enables an in-depth analysis of shaping the protagonists' identities. The findings reveal that both films challenge traditional norms and empower their female leads, demonstrating how media critiques and redefines cultural perceptions of gender and perfectionism. Ultimately, this study underscores film’s potential as a tool for raising awareness and fostering positive social change, emphasizing its role in shaping discourse around gender expectations and the pursuit of perfection.